Оценка висцеральной гемодинамики у больных циррозом печени после спленэктомии в сравнении с неоперированными больными в стадии декомпенсации - Тугушев, А. С.; Туманская, Н. В.; Гулевский, С. Н.; Черковская, О. С.; Киосов, А. М.; Тулупов, А. А.; Тугушев, Алій Саітович; Туманська, Наталя Валеріївна; Черковська, Ольга Степанівна (My University, 2015)
Проведена оценка влияния разобщающих оперативных вмешательств на характер изменений висцеральной гемодинамики у больных циррозом печени в сравнении с неоперированными больными в стадии декомпенсации. Показано, что характер изменений висцеральной гемодинамики после спленэктомии, в отличие от неоперированных больных, характеризуется снижением воротного давления вследствие уменьшения объема притекающей к печени висцеральной крови. Splenectomy in patients with cirrhosis presupposes an increase of blood inflow into portal system to decrease the portal pressure. At the same time there are different opinions about splenectomy. So it is actual to study the character of changes of blood flow in vessels of abdominal cavity in pre- and postsurgical periods and assessment of an influence of these changes on the clinical course of cirrhosis. Aim of research. To assess an influence of splenectomy on the character of changes of splanchnic hemodynamics in patients with cirrhosis comparing to non-operated patients with compensated and decompensated clinical course. Conclusion. The changes of splanchnic hemodynamics after splenectomy are characterized with decrease of the volume of splanchnic blood. The result is a decrease of portal pressure that is proved with decrease of congestion index in portal vein, decrease of tension of varicose veins, elimination of "red signs" and consequently elimination of the menace of relapse of bleeding and development of resistant ascites. At the same time splectomy can be done in patients with decompensated clinical course of cirrhosis that is proved with an absence of lethality in postsurgical period.
Keywords: цирроз печени; портальная гипертензия; висцеральный кровоток; спленэктомия; ультразвуковое сканирование; допплерография; cirrhosis; portal hypertension; splanchnic blood flow; splenectomy; ultrasound scanning; dopplerography